Antiinflammatory Activity from Marine Microalgae Chlorella vulgaris Extract Used Human Red Blood Cells Stability Method (HRBC) - Dewi kurnia; Nadya Prisdayanti; Lia Marliani; Idar Idar; Zeily Nurochman (Jurnal Kartika Kimia, 2019)
The biologic protection response against disruption in the body can be an inflammatory reaction. Medications commonly used to treat inflammation are steroids and non-steroids which, if used over a long period, can cause adverse side effects. Several studies have shown that microalgae can be used as an anti-inflammatory agent. This research was conducted to determine the anti-inflammatory activity of the Chlorella vulgaris microalgae extract. Extraction was carried out by multilevel maceration method using n-hexane, chloroform, and ethanol. TLC monitoring results showed that the Chlorella vulgaris extract contained flavonoid, phenol, alkaloid, and steroid saponin compounds. The anti-inflammatory activity test of the extract was carried out used Human Red Blood Cell (HRBC) stability method with Na-diclophenac as a comparison standard. The results showed the inhibition value of red blood cell hemolysis (IC50) in n-hexane, chloroform and ethanol extracts respectively 150,399; 83.852 and 92.349% with the inhibition value of Na-diclophenac standard of 55.149%. Chloroform extract is known to have the most active anti-inflammatory activity which is 83,852 ppm. The results of this study indicate that the chloroform extract in Chlorella vulgaris microalgae has the potential as an anti-inflammatory agent that can be developed as an alternative anti-inflammatory drug from natural marine materials. Keywords: anti-inflammatory, Chlorella vurlgaris, Human Red Blood Cells (HRBC)